Inhibition of JAK-STAT Signaling Pathway Alleviates Age-Related Phenotypes in Tendon Stem/Progenitor Cells - Chen, Minhao; Xiao, Longfei; Dai, Guangchun; Lu, Panpan; Zhang, Yuanwei; Li, Yingjuan; Ni, Ming; Rui, Yunfeng (Frontiers in Cell and Developmental Biology, 2021)
Diminished regeneration or healing capacity of tendon occurs during aging. It has been well demonstrated that tendon stem/progenitor cells (TSPCs) play a vital role in tendon maintenance and repair. Here, we identified an accumulation of senescent TSPCs in tendon tissue with aging. In aged TSPCs, the activity of JAK-STAT signaling pathway was increased. Besides, Genetic knockdown of JAK2 or STAT3 significantly attenuated TSPCs senescence in aged TSPCs. Pharmacological inhibition of JAK-STAT signaling pathway with AG490 similarly attenuated cellular senescence and senescence associated secretory phenotype (SASP) of aged TSPCs. In addition, inhibition of JAK-STAT signaling pathway also restored the age-related dysfunctions of TSPCs, including self-renewal, migration, actin dynamics and stemness. Together, our findings reveal the critical role of JAK-STAT signaling pathway in the regulation of TSPCs aging and suggest an ideal therapeutic target for the age-related tendon disorders.